Factors affecting online purchase intention of handcraft products: moderation of lifestyle - Triyono, Triyono; Susanto, Moh. Rusnoto; Barriyah, Insanul Qisti; Sofyan, Yayan; Saehu, Muh. Syaiful (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study aims to analyze the influence of digital marketing, brand image, and product variety on online purchase intentions of handicraft products moderated by lifestyle. Method – This study uses a quantitative method and a causally associative approach. Customers who made purchases of handcraft products in PT. Indo Risakti was the population in this study. The research sample comprised 155 respondents, measured using the Hair et al. approach and the purposive sampling technique. The survey method is used in data collection by providing online questionnaires to respondents to fill out. The data analysis technique used partial least squares-structural equality modeling (PLS-SEM) with SmartPLS as a statistical tool. Findings – The research findings show that brand image and lifestyle positively affect the interest in buying handicraft products online. In contrast, digital marketing and product variants do not affect the interest in buying handicraft products online. Lifestyle can strengthen the influence of digital marketing, brand image, and product variations on the interest in buying handicraft products online. Implications – Theoretically, this research has implications for enriching scientific literature on consumer behavior in online shopping, especially for handicraft products. Practically, it can guide business actors to develop more effective marketing strategies. Market segmentation based on lifestyle can help businesses target more appropriate and relevant consumers.